Graphene oxide coated bismuth ferrite anode material and preparation method thereof and negative electrode sheet
By using hydrophilic oxygenne on the surface of iron acid, graphene is used to solve the problem of high internal resistance and prone aging of ironic acid electrode materials, and the effect of reducing internal resistance, improving conductive and circulating performance.
Patent Information
- Application Number
- CN202411412106.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-11
AI Technical Summary
As an electrode material, bismuth ferrate has problems such as high internal resistance, easy aging and effective substance loss, resulting in serious capacity decay of lithium-ion batteries during circulation.
The hydraulic oxygenne graphene is covered through the surface of the iron acid pyrite to form the iron -olsum olored material covered by the oxide graphene, reducing the internal resistance and increasing conductivity.
Reduced the internal resistance of iron acid, improved the conductivity and circulation performance, reduced the enrichment of metal BI and the loss of active substances, and extended the service life of the battery.
Smart Images

Figure CN118929770B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a graphene oxide-coated bismuth ferrite anode material, a preparation method thereof, and a negative electrode sheet. Background Art
[0002] Bismuth ferrite is a common multiferroic material and is widely used in the field of ferroelectrics. As one of the transition metal oxides, bismuth ferrite has a stable perovskite structure. The theoretical specific capacity of bismuth ferrite is 770 mAh g -1 , which is almost twice the capacity of the commonly used negative electrode material graphite. In addition, as a conversion negative electrode material, the volume change of bismuth ferrite during the cycle is reversible, which is safer than embedded graphite and other negative electrode materials. Therefore, bismuth ferrite is expected to become a stable negative electrode material for lithium-ion batteries. However, there are very few studies on bismuth ferrite as an electrode material. One reason is that bismuth ferrite itself is an insulator with a large internal resistance; the second reason is that even as an electrode material, the negative electrode material is consumed in large quantities during the growth of the solid electrolyte interface (SEI), resulting in aging of the electrode material; the formation of new phases and the diffusion of iron ions to the surface of the material further lead to the loss of effective substances, and ultimately lead to serious capacity decay of the battery during the cycle.
[0003] In view of this, in order to reduce internal resistance, prevent electrode aging, reduce effective material loss, and at the same time, inhibit the precipitation of metal elements during the charge and discharge cycle process, so as to realize the application prospects of bismuth ferrite in negative electrode materials and give full play to its material advantages and potential, the present invention is specially proposed. Summary of the invention
[0004] The object of the present invention is to provide a graphene oxide-coated bismuth ferrite anode material and a preparation method and a negative electrode sheet thereof, so as to improve the above-mentioned technical problems.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a method for preparing a graphene oxide-coated bismuth ferrite anode material, comprising: coating graphene oxide on the surface of bismuth ferrite by a hydrothermal method, wherein the mass ratio of graphene oxide to bismuth ferrite is 15:(0.8~1.2), and the bismuth ferrite is bismuth ferrite with a blocky morphology prepared by a hydrothermal method.
[0007] Optionally, the preparation step of bismuth ferrite includes: dissolving iron salt and bismuth salt, adding dropwise a precipitant solution to generate a precipitate, and then dissolving the precipitate again in a first mineralizer solution and performing a hydrothermal reaction.
[0008] Optionally, the iron salt is selected from iron nitrate, the bismuth salt is selected from bismuth nitrate, and the solvent used to dissolve the iron salt and the bismuth salt is a nitric acid solution with a mass concentration of 8% to 12%;
[0009] Optionally, the precipitant solution is a 1.5M to 2.5M sodium hydroxide solution;
[0010] Optionally, the first mineralizer solution is a 4M to 10M sodium hydroxide solution;
[0011] Optionally, the temperature of the hydrothermal reaction for preparing the bismuth ferrite is 200° C. to 240° C., and the reaction time is 12 to 24 hours.
[0012] Optionally, the first mineralizer solution is a 6M to 8M sodium hydroxide solution, the temperature of the hydrothermal reaction for preparing bismuth ferrite is 220° C. to 240° C., and the reaction time is 12 to 24 hours.
[0013] Optionally, before the hydrothermal reaction, the generated precipitate is subjected to ultrasonic treatment, stirred, centrifuged and separated, and then the precipitate is washed multiple times.
[0014] Optionally, coating graphene oxide on the surface of bismuth ferrite by a hydrothermal method includes: dispersing bismuth ferrite and graphene oxide powder in water, and then adding a second mineralizer solution to perform a hydrothermal reaction.
[0015] Optionally, the hydrothermal reaction temperature of the coated graphene oxide is 160°C to 200°C, and the reaction time is 12h to 24h. The second mineralizer solution is a 0.8-1.2M sodium hydroxide solution, and the ratio of sodium hydroxide to the bismuth ferrite is 3-5:1.
[0016] Optionally, the method for preparing the graphene oxide-coated bismuth ferrite anode material further comprises: repeatedly washing the bismuth ferrite anode material obtained after coating the graphene oxide with deionized water and alcohol, and drying it at a temperature of 75° C. to 85° C. for at least 12 hours.
[0017] In a second aspect, the present invention further provides a graphene oxide-coated bismuth ferrite anode material, which is prepared by the above-mentioned method for preparing the graphene oxide-coated bismuth ferrite anode material.
[0018] In a third aspect, the present invention further provides a negative electrode sheet, the electrode active material of which is the above-mentioned graphene oxide-coated bismuth ferrite anode material.
[0019] The present invention has the following beneficial effects: by specifically selecting bismuth ferrite with a blocky morphology prepared by a hydrothermal method as a matrix of a negative electrode material, the bismuth ferrite has high crystallinity and orderly arranged crystals and high thermal stability; after the bismuth ferrite with a specific morphology is coated and modified by a specific proportion of graphene oxide, the internal resistance of the bismuth ferrite can be reduced, so that the anode material formed by the coating has good conductivity; and the coating of graphene oxide can also reduce the enrichment of metal Bi on the surface of the material, avoid the loss of active substances, thereby making it possible to industrialize bismuth ferrite as a negative electrode active material, and improving the application value of bismuth ferrite. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 XRD comparison diagram of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1;
[0022] Figure 2 XRD comparison diagram of bismuth ferrite samples of Example 2 to Example 4 of the present invention;
[0023] Figure 3 XRD comparison diagram of bismuth ferrite samples of Examples 5 to 8 of the present invention;
[0024] Figure 4 XRD comparison diagram of bismuth ferrite samples of Example 1 and Example 9 of the present invention;
[0025] Figure 5 The thermogravimetric and heat flow results of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention are shown;
[0026] Figure 6 This is a SEM image of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention;
[0027] Figure 7 This is a SEM image of BiFeO3-GO obtained in Example 1 of the present invention;
[0028] Figure 8 This is the XPS graph of Bi of the bismuth acid sample obtained in step (5) of Example 1 of the present invention after the first cycle is completed;
[0029] Fig. 9This is a diagram showing the valence state changes of BiFeO3-GO during the first cycle of Example 1 of the present invention;
[0030] Fig.10 The current of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1 is 0.1 A g -1 Cycle capacity diagram of ;
[0031] Fig.11 The current size of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1 is 1 A g -1 Cycle capacity diagram of ;
[0032] Fig.12 The current of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1 is 0.1 A g -1 ~1.6 A g -1 The charge and discharge curve diagram of
[0033] Fig.13 The electrochemical impedance diagrams of the bismuth ferrite sample obtained in step (5) of Example 1 of the present invention, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1;
[0034] Fig.14 This is a comparison chart of the cycle performances of BiFeO3-GO obtained in Example 1 of the present invention, BiFeO3-0.5GO obtained in Comparative Example 2, and BiFeO3-2GO obtained in Comparative Example 3;
[0035] Fig.15 The current of BiFeO3-GO obtained in Example 1 of the present invention and Comparative Examples 4-5 is 1 A g -1 Cycle capacity diagram of . DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] The following is a detailed description of a graphene oxide-coated bismuth ferrite anode material, a preparation method thereof, and a negative electrode sheet provided by the present invention.
[0038] Some embodiments of the present invention provide a method for preparing a graphene oxide-coated bismuth ferrite anode material, which comprises: coating graphene oxide on the surface of bismuth ferrite by a hydrothermal method, wherein the mass ratio of graphene oxide to bismuth ferrite is 15:(0.8~1.2), and the bismuth ferrite is bismuth ferrite with a blocky morphology prepared by a hydrothermal method.
[0039] In order to enable bismuth ferrite to meet the application requirements as a negative electrode material through modification, the inventors, through a lot of research and practice, first selected bismuth ferrite with a special morphology prepared by a specific method for modification, that is, bismuth ferrite prepared by a hydrothermal method. The prepared bismuth ferrite with a block morphology has a high degree of crystallinity, which enables it to have a certain conductivity, and its block morphology indicates that its crystals are arranged in an orderly manner, so that it has a low expansion coefficient, and at the same time has a high thermal stability temperature, and is not prone to melting and decomposition structural changes. By coating and modifying it with graphene oxide, the internal resistance of the bismuth ferrite material can be reduced, and the transmission efficiency of battery cations can be improved. At the same time, graphene oxide can also prevent the metal element Bi from being enriched on the surface of the material. It should be noted that the inventors found in the coating modification research of the bismuth ferrite that it cannot refer to some traditional graphene coating modification methods, and use a small amount of graphene for surface coating, which cannot achieve effective modification effect, but needs to use more graphene powder to achieve the coating of bismuth ferrite, and the mass ratio of graphene oxide to bismuth ferrite reaches 15: (0.8~1.2). And based on this dosage, if the amount of graphene oxide is too small, the internal resistance of the material is not greatly improved, the coating amount is small, and the cycle performance is not significantly improved; if the amount of graphene oxide is too much, the initial capacity will be reduced, and too much coating will cause the generation of new interfaces, and the interface resistance exceeds the reduction of internal resistance provided by graphene oxide, resulting in no further improvement in the internal resistance of the coated modified material.
[0040] Specifically, in some embodiments, the preparation step of bismuth ferrite includes: dissolving iron salt and bismuth salt, adding a precipitant solution dropwise to generate a precipitate, and then dissolving the precipitate again in a first mineralizer solution and performing a hydrothermal reaction.
[0041] For reference, the iron salt is selected from ferric nitrate, the bismuth salt is selected from bismuth nitrate, and the solvent used to dissolve the iron salt and the bismuth salt is a nitric acid solution with a mass concentration of 8% to 12%.
[0042] In some embodiments, the precipitant solution is a 1.5M to 2.5M sodium hydroxide solution, such as a 2M sodium hydroxide solution; the first mineralizer solution is a 4M to 10M sodium hydroxide solution, such as a 4M sodium hydroxide solution, a 5M sodium hydroxide solution, a 6M sodium hydroxide solution, a 7M sodium hydroxide solution, an 8M sodium hydroxide solution, a 9M sodium hydroxide solution or a 10M sodium hydroxide solution, etc. The selection of the concentration of the first mineralizer solution is conducive to the generation of bismuth ferrite with higher purity.
[0043] In some embodiments, the temperature of the hydrothermal reaction for preparing bismuth ferrite is 200°C to 240°C, such as 200°C, 210°C, 220°C, 230°C or 240°C, or between any two of the above temperatures, and the reaction time is 12 to 24h, such as 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h, etc. By selecting the above hydrothermal reaction temperature and reaction time, the hydrothermal reaction can be more sufficient, and the purity of the obtained bismuth ferrite is higher.
[0044] In order to further improve the purity of bismuth ferrite, in some embodiments, the first mineralizer solution is a 6M~8M sodium hydroxide solution, the temperature of the hydrothermal reaction for preparing the bismuth ferrite is 220°C~240°C, and the reaction time is 12~24 hours.
[0045] In some embodiments, before the hydrothermal reaction, the generated precipitate is ultrasonicated, stirred, centrifuged and precipitated, and then the precipitate is washed multiple times. Ultrasound can make the precipitate particles more evenly dispersed, prevent particle agglomeration, and also help to remove impurities and adsorbents on the particle surface. Multiple washings can further remove impurities and improve the purity of the product. Deionized water is used for repeated washing.
[0046] Further, in order to effectively coat the surface of the block-shaped bismuth ferrite with graphene oxide and form a specific coating layer with a certain pore structure, in some embodiments, coating the surface of the bismuth ferrite with graphene oxide by a hydrothermal method includes: dispersing bismuth ferrite and graphene oxide powder in water, and then adding a second mineralizer solution for hydrothermal reaction. The second mineralizer solution can be selected as a 0.8-1.2M sodium hydroxide solution.
[0047] In some embodiments, the hydrothermal reaction temperature of the coated graphene oxide is 160°C to 200°C, for example, 160°C, 170°C, 180°C, 190°C or 200°C, or a temperature between any of the above temperatures, and the reaction time is 12h to 24h, for example, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h, etc.
[0048] Further, in some embodiments, the method for preparing the graphene oxide coated bismuth ferrite anode material further comprises: washing the bismuth ferrite anode material obtained after coating the graphene oxide repeatedly with deionized water and alcohol, and drying at a temperature of 75°C to 85°C for at least 12 hours. Impurities can be removed by washing and drying, thereby improving the quality of the product. Alcohol can be selected from industrial alcohol or anhydrous ethanol.
[0049] Some embodiments of the present invention also provide a graphene oxide-coated bismuth ferrite anode material, which is prepared by the above-mentioned method for preparing the graphene oxide-coated bismuth ferrite anode material. The bismuth ferrite anode material has a core of bismuth ferrite, and its surface is coated with graphene oxide. The material has a better specific surface area and can provide more active sites, thereby greatly alleviating the capacity attenuation problem of the electrode material, reducing the internal resistance of the material, improving the conductivity of the material, and improving the coulombic efficiency, thereby improving the overall cycle performance of the material.
[0050] Some embodiments of the present invention further provide a negative electrode sheet, whose electrode active material is the above-mentioned graphene oxide-coated bismuth ferrite anode material. The negative electrode sheet generally includes a current collector, on which a corresponding negative electrode material is coated, wherein the negative electrode material includes a negative electrode active substance, i.e., an electrode active material of an embodiment of the present invention, a conductive additive, and a binder, etc.
[0051] Some other embodiments of the present invention may also provide a lithium-ion battery comprising the negative electrode sheet of the above embodiment.
[0052] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0053] The graphene oxide powder and reduced graphene oxide powder of the following examples and comparative examples were purchased from MacLean.
[0054] Example 1
[0055] This embodiment provides a method for preparing a graphene oxide-coated bismuth ferrite anode material, which comprises the following steps:
[0056] (1) Dissolve 2.0404 g of ferric nitrate and 2.4499 g of bismuth nitrate in 20 mL of solvent (10% dilute nitric acid solution) and stir thoroughly until completely dissolved.
[0057] (2) Add 2M sodium hydroxide solution dropwise to the solution obtained in step (1) until a precipitate is formed.
[0058] (3) Ultrasonicate the precipitate, stir it thoroughly, and then centrifuge it to precipitate it. Then, wash the precipitate repeatedly with deionized water.
[0059] (4) The washed precipitate from step (3) was dissolved in a 6M sodium hydroxide solution, and the dissolved solution was placed in a reactor for hydrothermal reaction for 12 hours at a temperature of 240°C.
[0060] (5) The bismuth ferrite sample obtained in step (4) is repeatedly washed with anhydrous ethanol and deionized water and dried for later use.
[0061] (6) The bismuth ferrite sample obtained in step (5) and the graphene oxide powder were mixed in a mass ratio of 1:15, added to deionized water, and ultrasonicated until uniformly dispersed.
[0062] (7) Add 50 mL of 1 M sodium hydroxide solution to the dispersion in step (6) and place in a reactor for secondary hydrothermal reaction for 12 h at a temperature of 180 °C.
[0063] (8) The sample obtained in step (7) was repeatedly washed with deionized water and anhydrous ethanol, and then dried in an oven at 80° C. for 12 h to obtain a graphene oxide-coated bismuth ferrite anode material (denoted as BiFeO3-GO).
[0064] Example 2
[0065] This embodiment provides a method for preparing a graphene oxide-coated bismuth ferrite anode material, which comprises the following steps:
[0066] (1) Dissolve 2.0404 g of ferric nitrate and 2.4499 g of bismuth nitrate in 20 mL of solvent (10% dilute nitric acid solution) and stir thoroughly until completely dissolved.
[0067] (2) Add 2M sodium hydroxide solution dropwise to the solution obtained in step (1) until a precipitate is formed.
[0068] (3) Ultrasonicate the precipitate, stir it thoroughly, and then centrifuge it to precipitate it. Then, wash the precipitate repeatedly with deionized water.
[0069] (4) The washed precipitate from step (3) was dissolved in a 4M sodium hydroxide solution, and the dissolved solution was placed in a reactor for hydrothermal reaction for 12 h at a temperature of 200°C.
[0070] (5) The bismuth ferrite sample obtained in step (4) is repeatedly washed with anhydrous ethanol and deionized water and dried for later use.
[0071] (6) The bismuth ferrite sample obtained in step (5) and the graphene oxide powder were mixed in a mass ratio of 1:15, added to deionized water, and ultrasonicated until uniformly dispersed.
[0072] (7) Add 50 mL of 1 M sodium hydroxide solution to the dispersion in step (6) and place in a reactor for secondary hydrothermal reaction for 12 h at a temperature of 180 °C.
[0073] (8) The sample obtained in step (7) was repeatedly washed with deionized water and anhydrous ethanol, and then dried in an oven at 80° C. for 12 h to obtain a graphene oxide-coated bismuth ferrite anode material (denoted as BiFeO3-GO).
[0074] Example 3
[0075] This embodiment provides a method for preparing a graphene oxide-coated bismuth ferrite anode material, which comprises the following steps:
[0076] (1) Dissolve 2.0404 g of ferric nitrate and 2.4499 g of bismuth nitrate in 20 mL of solvent (10% dilute nitric acid solution) and stir thoroughly until completely dissolved.
[0077] (2) Add 2M sodium hydroxide solution dropwise to the solution obtained in step (1) until a precipitate is formed.
[0078] (3) Ultrasonicate the precipitate, stir it thoroughly, and then centrifuge it to precipitate it. Then, wash the precipitate repeatedly with deionized water.
[0079] (4) The washed precipitate from step (3) was dissolved in a 4M sodium hydroxide solution, and the dissolved solution was placed in a reactor for hydrothermal reaction for 12 hours at a temperature of 220°C.
[0080] (5) The bismuth ferrite sample obtained in step (4) is repeatedly washed with anhydrous ethanol and deionized water and dried for later use.
[0081] (6) The bismuth ferrite sample obtained in step (5) and the graphene oxide powder were mixed in a mass ratio of 1:15, added to deionized water, and ultrasonicated until uniformly dispersed.
[0082] (7) Add 50 mL of 1 M sodium hydroxide solution to the dispersion in step (6) and place in a reactor for secondary hydrothermal reaction for 12 h at a temperature of 180 °C.
[0083] (8) The sample obtained in step (7) was repeatedly washed with deionized water and anhydrous ethanol, and then dried in an oven at 80° C. for 12 h to obtain a graphene oxide-coated bismuth ferrite anode material (denoted as BiFeO3-GO).
[0084] Example 4
[0085] This embodiment provides a method for preparing a graphene oxide-coated bismuth ferrite anode material, which comprises the following steps:
[0086] (1) Dissolve 2.0404 g of ferric nitrate and 2.4499 g of bismuth nitrate in 20 mL of solvent (10% dilute nitric acid solution) and stir thoroughly until completely dissolved.
[0087] (2) Add 2M sodium hydroxide solution dropwise to the solution obtained in step (1) until a precipitate is formed.
[0088] (3) Ultrasonicate the precipitate, stir it thoroughly, and then centrifuge it to precipitate it. Then, wash the precipitate repeatedly with deionized water.
[0089] (4) The washed precipitate from step (3) was dissolved in a 4M sodium hydroxide solution, and the dissolved solution was placed in a reactor for hydrothermal reaction for 12 hours at a temperature of 240°C.
[0090] (5) The bismuth ferrite sample obtained in step (4) is repeatedly washed with anhydrous ethanol and deionized water and dried for later use.
[0091] (6) The bismuth ferrite sample obtained in step (5) and the graphene oxide powder were mixed in a mass ratio of 1:15, added to deionized water, and ultrasonicated until uniformly dispersed.
[0092] (7) Add 50 mL of 1 M sodium hydroxide solution to the dispersion in step (6) and place in a reactor for secondary hydrothermal reaction for 12 h at a temperature of 180 °C.
[0093] (8) The sample obtained in step (7) was repeatedly washed with deionized water and anhydrous ethanol, and then dried in an oven at 80° C. for 12 h to obtain a graphene oxide-coated bismuth ferrite anode material (denoted as BiFeO3-GO).
[0094] Example 5
[0095] The only difference between this embodiment and embodiment 4 is that the concentration of the sodium hydroxide solution in step (4) is 6M.
[0096] Example 6
[0097] The only difference between this embodiment and embodiment 4 is that the concentration of the sodium hydroxide solution in step (4) is 7M.
[0098] Example 7
[0099] The only difference between this embodiment and embodiment 4 is that the concentration of the sodium hydroxide solution in step (4) is 8M.
[0100] Example 8
[0101] The only difference between this embodiment and embodiment 4 is that the concentration of the sodium hydroxide solution in step (4) is 10M.
[0102] Example 9
[0103] The only difference between this embodiment and embodiment 1 is that the hydrothermal reaction time in step (4) is 24 hours.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that reduced graphene oxide is used instead of graphene oxide in step (6), and the obtained composite material is recorded as BiFeO3-rGO.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that in step (6), the bismuth ferrite sample and the graphene oxide powder are in a mass ratio of 1:30, and the obtained composite material is recorded as BiFeO3-0.5GO.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 1 is that in step (6), the bismuth ferrite sample and the graphene oxide powder are in a mass ratio of 2:15, and the obtained composite material is recorded as BiFeO3-2GO.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 1 is that the bismuth ferrite sample in step (6) is prepared by the sol-gel method, and the obtained composite material is recorded as BiFeO3-sol-gel method. The specific preparation process of the bismuth ferrite sample is as follows: the raw materials are ferric nitrate (Fe(NO)3·9H2O), bismuth nitrate (Bi(NO)3·5H2O), deionized water and dilute nitric acid (mass concentration is 10%). The molar ratio of iron bismuth ions (Fe / Bi) is 1:1. A 0.1M aqueous solution of bismuth nitrate is prepared. Due to the hydrolysis of bismuth nitrate, an appropriate amount of dilute nitric acid is added dropwise to form a transparent and colorless solution. The same mole of ferric nitrate is weighed and added to the solution, and an appropriate amount of citric acid is used as a chelating agent (the molar ratio with the metal cation is 3:2). After stirring for ten minutes, it is placed in a water bath at 70°C for 3h to form a brown transparent gel, which is then dried at 120°C for 12 hours. A brown precursor was obtained, ground, and sintered at different temperatures with a heating rate of 5°C / min and kept warm for 2h. The sample was then taken out and ground to obtain BiFeO3.
[0112] Comparative Example 5
[0113] The difference between this comparative example and Example 1 is that the bismuth ferrite sample in step (6) is prepared by a melting method, and the obtained composite material is recorded as BiFeO3-melting method. The specific preparation process of the bismuth ferrite sample is as follows: the raw materials are Bi2O3 (99.99%, powder, Aladdin), Fe2O3 (99.5%, powder, Aladdin), and polyvinyl butyral (PVB, 15.0-18.0, butyraldehyde 70-75%, powder, Aladdin), and ethanol is added to a mortar for mixing and grinding, the molar ratio of Bi2O3 to Fe2O3 is 1:1, and 3wt% PVB is added as a binder. The mixed powder is placed in a mold with a diameter of 15 mm, and an electric desktop tablet press is used to maintain the pressure at a pressure of 8 MPa for 5 minutes to obtain a disc. The pressed disc is placed in an alumina crucible and sintered in a muffle furnace. The heating rate was 5°C / min. After the insulation was completed, the temperature was reduced to 500°C at a rate of 1°C / min and then cooled in the furnace to obtain BiFeO3 blocks.
[0114] Test Example 1
[0115] The bismuth ferrite sample obtained in step (5) of Example 1, the BiFeO3-GO obtained in Example 1, the BiFeO3 obtained in Examples 1-9, and the BiFeO3-rGO obtained in Comparative Example 1 were subjected to XRD analysis. The XRD patterns of the bismuth ferrite sample obtained in step (5) of Example 1, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peak of BiFeO3 corresponds to the PDF card (PDF#22-0169), and it can be determined that 2θ=22.49 ◦ , 31.80 ◦ and 32.13 ◦ The characteristic peaks correspond to the (101), (012) and (110) crystal planes of BiFeO3. From the peak shape, it can be seen that the diffraction peaks are very sharp. The XRD patterns of the bismuth ferrite samples of Examples 2 to 4 are shown in FIG. Figure 2 The XRD patterns of bismuth ferrite shown in Examples 5 to 8 are as follows: Figure 3 As shown, the XRD patterns of the bismuth ferrite samples of Example 1 and Example 9 are as follows: Figure 4 As shown. Figure 2-Figure 4 It can be seen that the mineralizer solution is a sodium hydroxide solution with a concentration of 6M~8M, the temperature of the hydrothermal reaction is 220℃~240℃, and the reaction time is 12~24 hours, which is beneficial to ensure the purity of the bismuth ferrite sample.
[0116] Test Example 2
[0117] The bismuth ferrite sample obtained in step (5) of Example 1 was subjected to thermogravimetric and heat flow tests. The thermogravimetric and heat flow results are shown in the figure below: Figure 5 As shown, from Figure 5 It can be seen that the bismuth ferrite sample has high thermal stability and is not prone to melting and decomposition and structural changes. The bismuth ferrite sample obtained in step (5) of Example 1 and the BiFeO3-GO obtained in Example 1 were observed by scanning electron microscopy, and the results are as follows: Figure 6 and Figure 7 As shown. Figure 6 It can be seen that the BiFeO3 sample is blocky and has obvious agglomeration. Figure 7 It can be seen that graphene oxide is coated on the BiFeO3 surface in a layered structure.
[0118] Test Example 3
[0119] Battery assembly: First, the electrode material and acetylene black are fully ground and mixed in a mortar, and then sodium alginate (SA) is added for further grinding and mixing, and the ratio of the three is 8:1:1. Deionized water is added dropwise to prepare a slurry, and then the slurry is coated on the anode-specific copper foil, dried at 80°C in a vacuum drying oven for 12 hours, and taken out for cutting. The electrolyte consists of 1 mol / L LiPF6 and EC:DMC:DEC (volume ratio 1:1:1). Polypropylene (PP) microporous membrane is used as a diaphragm and lithium metal sheet is used as an electrode. Finally, the 2032 button battery is assembled in an argon protection glove box. Among them, the electrode materials are selected from the bismuth ferrite sample obtained in step (5) of Example 1, the BiFeO3-GO obtained in Example 1, and the graphene-coated bismuth ferrite anode material obtained in Comparative Examples 1-5.
[0120] Performance test: Connect the assembled electrode sheet to the blue electric test system, set the voltage window to 0.01~3V, and select the current density to 0.1A g -1 , test the cross-current charge-discharge cycle. Continue to set the current density to 0.1 A g -1 ~2 A g -1 , test rate charge and discharge cycle.
[0121] The XPS graph of Bi of the bismuth ferrite sample obtained in step (5) of Example 1 after the first cycle is as follows: Figure 8 The valence state of the BiFeO3-GO obtained in Example 1 during the first cycle is shown in Fig. 9 As shown. Figure 8 and Fig. 9 By comparison, it can be seen that the coating of graphene oxide can reduce the enrichment of metal Bi on the negative electrode surface and thus reduce the loss of active substances.
[0122] The current of the bismuth ferrite sample obtained in step (5) of Example 1, the BiFeO3-GO obtained in Example 1, and the BiFeO3-rGO obtained in Comparative Example 1 is 0.1 A g -1 The cycle capacity diagram is as follows Fig.10 As shown, the current is 1 A g -1 The cycle capacity diagram is as follows Fig.11 As shown, the current is 0.1 A g -1 ~1.6 A g -1 The charge and discharge curve is as follows Fig.12 The electrochemical impedance spectroscopy diagram is shown in Fig.13 shown.
[0123] from Fig.10 It can be seen that after 50 cycles of testing, BiFeO3-GO showed a high capacity of 562.8 mAh g -1 The high capacity performance of BiFeO3 was reduced to 277.4 mAh g -1 .from Fig.11 It can be seen that at 1 A g -1 At the current density of 1.344 W / m, the capacity of BiFeO3-GO was 161.6 mAh g after 500 cycles. -1 Still better than BiFeO3 (109.3 mAh g -1 ).from Fig.12 It can be seen that as the current density increases from 100, 200, 400, 800 to 1600 mA g -1 , the discharge of BiFeO3-GO is more stable, indicating that BiFeO3-GO exhibits excellent rate performance. Fig.13 It can be seen that the Nyquist circle of BiFeO3-GO is smaller than that of FTO, so it has a smaller internal resistance. Figure 10-13 From the comparison, it can be seen that the coating with graphene oxide is obviously better than that with reduced graphene oxide. First, due to the lack of oxygen, the storage capacity of reduced graphene oxide for lithium ions is low, which can be seen from the initial capacity of its cycle performance. Secondly, the internal resistance of the composite materials coated with reduced graphene and graphene oxide is similar, but graphene oxide provides additional electrochemical activity due to the role of oxygen functional groups. Finally, graphene oxide has better stability in the electrolyte.
[0124] The cycling performance comparison of BiFeO3-GO obtained in Example 1, BiFeO3-0.5GO obtained in Comparative Example 2 and BiFeO3-2GO obtained in Comparative Example 3 is shown in FIG. Fig.14 As shown. Among them, (a) is the current size of 0.1 A g -1 Cyclic capacity diagram of (b) when the current is 1 A g -1Cyclic capacity diagram of the current size of 0.1 A g -1 ~1.6 A g -1 (d) is the charge and discharge curve of the electrochemical impedance spectroscopy. Fig.14 It can be seen that excessive or low graphene doping will affect the performance of the negative electrode material. When it is too low, the internal resistance of the material is not greatly improved. At the same time, the coating amount is small and the cycle performance is not significantly improved. When the coating is too much, obvious initial capacity loss can be found. This is due to the weak lithium storage capacity of graphene oxide. At the same time, when the coating is too much, due to the generation of new interfaces, the interface resistance exceeds the reduction in internal resistance provided by graphene oxide, resulting in no further improvement in the internal resistance of the composite material.
[0125] Comparison of the cycle performance of BiFeO3-GO obtained in Example 1 and Comparative Examples 4-5 Fig.15 As shown, from Fig.15 It can be seen that the sample prepared under hydrothermal conditions has a higher capacity at 1000 mAh g after being coated with graphene oxide. -1 At a current density of , the capacity after 500 cycles is significantly better than that of other different preparation methods under the same conditions.
[0126] In summary, the present invention uses a double hydrothermal method to prepare the BiFeO3-GO composite anode material. The preparation method is simple to operate, has a fast synthesis speed, and has stable synthesis components. Compared with directly using BiFeO3 as the anode material, the current density is 100 mAhg -1 The initial electrochemical capacity is as high as 1774.4 mAh g -1 After 50 cycles, the capacity still reaches 662.8 mAh g -1 It is twice that of BiFeO3 under the same conditions.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphene oxide-coated bismuth ferrite anode material, characterized in that: It includes: Graphene oxide is coated on the surface of bismuth ferrite by a hydrothermal method, wherein the mass ratio of the graphene oxide to the bismuth ferrite is 15:(0.8-1.2), and the bismuth ferrite is a bismuth ferrite with a blocky morphology prepared by a hydrothermal method, and the preparation steps of the bismuth ferrite include: after dissolving an iron salt and a bismuth salt, a precipitant solution is added dropwise to generate a precipitate, and then the precipitate is dissolved again in a first mineralizer solution and then subjected to a hydrothermal reaction, the precipitant solution is a 1.5M-2.5M sodium hydroxide solution, the first mineralizer solution is a 6M-8M sodium hydroxide solution, the temperature of the hydrothermal reaction for preparing the bismuth ferrite is 220°C-240°C, and the reaction time is 12-24h; The method of coating graphene oxide on the surface of bismuth ferrite by a hydrothermal method includes: dispersing the bismuth ferrite and graphene oxide powder in water, and then adding a second mineralizer solution for hydrothermal reaction, wherein the hydrothermal reaction temperature of the graphene oxide coating is 160° C. to 200° C., and the reaction time is 12 h to 24 h; the second mineralizer solution is a 0.8 to 1.2 M sodium hydroxide solution, and the dosage ratio of sodium hydroxide to the bismuth ferrite is 3 to 5:
1.
2. The method for preparing the graphene oxide-coated bismuth ferrite anode material according to claim 1, characterized in that: The iron salt is selected from ferric nitrate, the bismuth salt is selected from bismuth nitrate, and the solvent used to dissolve the iron salt and the bismuth salt is a nitric acid solution with a mass concentration of 8% to 12%.
3. The method for preparing the graphene oxide-coated bismuth ferrite anode material according to claim 1, characterized in that: Before the hydrothermal reaction, the generated precipitate is subjected to ultrasonic treatment, stirred and centrifuged to separate the precipitate, and then the precipitate is washed multiple times.
4. The method for preparing the graphene oxide-coated bismuth ferrite anode material according to claim 1, characterized in that: Also includes: The bismuth ferrite anode material obtained after coating with graphene oxide was repeatedly washed with deionized water and alcohol, and then dried at a temperature of 75° C. to 85° C. for at least 12 hours.
5. A graphene oxide-coated bismuth ferrite anode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 4.
6. A negative electrode sheet, characterized in that: The electrode active material is the graphene oxide-coated bismuth ferrite anode material as described in claim 5.
Citation Information
Patent Citations
Bismuth ferrite-graphene compounding magnetism visible light catalyst, as well as preparation method and application of same
CN102626634A
Composition and preparation method thereof
CN107946563A